Resource Adjustment Costs, Cost Stickiness, and Value Creation in Mergers and Acquisitions* - Jang, Youngki; Yehuda, Nir (Contemporary Accounting Research, 2021)
ABSTRACT We examine whether resource adjustment costs, such as installation and disposal costs for fixed assets, or hiring and firing costs for employees, impede value creation in mergers and acquisitions (M&A). We focus on M&A deals because they are major corporate investment decisions. As a proxy for adjustment costs, we use a firm‐level measure of cost stickiness. We predict that acquirers with high adjustment costs have less flexibility in restructuring resources following the acquisition and will find it more costly to merge the target firm's operations. Consistent with this prediction, we find that the acquirer's adjustment costs are negatively associated with abnormal returns around the acquisition announcement. Additionally, adjustment costs are also negatively associated with deal synergies. Relatedly, we find that acquirers with high adjustment costs purchase targets with high adjustment costs. In accordance with this finding, we show that acquirers with high adjustment costs purchase intangible‐intensive targets. Collectively, our results highlight the important implication of adjustment costs in M&A deals for managers and capital market participants.